Safety and efficacy of immune checkpoint inhibitor cancer therapy in patients with preexisting type 1 diabetes mellitus - Hilder, Robin; Tsai, Karen; Quandt, Zoe; Isaacs, Dayna; Drakaki, Alexandra; Xing, Yan; In, Gino K.; Angell, Trevor E.; Lechner, Melissa G. (Frontiers in Endocrinology, 2023)
Introduction: Immune checkpoint inhibitors (ICI) produce dramatic tumor shrinkage and durable responses in many advanced malignancies, but their use is limited by the development of immune related adverse events (IRAEs) that occur in up to 60% of patients and often affect endocrine organs. Concern for more severe IRAEs in patients with pre-existing autoimmune diseases, including type 1 diabetes mellitus (T1DM), has led to the exclusion of such individuals from clinical trials of ICI therapy. As a result, little is known about the safety and efficacy of ICI in this population. Here, we report safety and treatments outcomes in ICI-treated patients with pre-existing T1DM. Methods: This retrospective case-controlled study evaluated adult patients with T1DM who received ICI therapy for solid malignancies from 2015-2021 at four academic medical centers. Patients with prior ICI therapy, bone marrow transplantation, or pregnancy were excluded. We collected data on demographics, cancer diagnosis and treatment, IRAE incidence and severity, and diabetes management. Controls were matched 2:1 by age, sex, cancer diagnosis and ICI therapy. Results: Of 12,142 cancer patients treated with ICI therapy, we identified 11 with a pre-existing confirmed diagnosis of T1DM prior to starting ICI therapy. Mean age was 50.6 years, 63.6% were female, and most received anti-PD1/PDL1 monotherapy (10/11) compared to combination therapy (1/11). Grade 3/4 IRAEs were seen in 3/11 subjects with pre-existing T1DM and were hepatitis, myositis, myasthenia gravis. All three cases had interruption of ICI therapy and administration of adjunct therapies including steroids, IVIG, or mycophenolate mofetil with resolution of the IRAE. The odds of all-grade IRAEs and of severe IRAEs were comparable between cases and controls matched for age, sex, cancer type and ICI therapy [OR 0.83 (95% CI 0.2-3.56), p=0.81, and OR 1.69 (0.31-9.36), p=0.55, respectively]. Overall survival was not different between patients with T1DM and controls (p=0.54). No patients had hospitalizations for diabetes-related complications during therapy. Discussion: These data suggest that ICI monotherapy can successfully be used in patients with pre-existing T1DM, with IRAE rates comparable to individuals without pre-existing T1DM. Larger, prospective studies of these potentially life-saving ICI therapies that include patients with pre-existing autoimmunity are warranted.